Current practice in nutrition after allogeneic hematopoietic stem cell transplantation – Results from a survey among hematopoietic stem cell transplant centers. Issue 4 (April 2021) - Toenges, R.; Greinix, H.; Lawitschka, A.; Halter, J.; Baumgartner, A.; Simon, A.; Arends, J.; Jäger, P.; Middeke, M.; Hilgendorf, I.; Klein, S.; Wagner-Drouet, E.M.; et al.
Summary: Background: Allogeneic hematopoietic stem cell transplantation (alloHSCT) is frequently associated with impaired oral intake and malnutrition, which potentially increases morbidity and mortality. Therefore, nutrition is one of the major challenges in the post-transplant period. Methods: To document the current clinical approach in nutritional treatment, we designed a questionnaire concerning the current practice in nutrition after alloHSCT and distributed it to German speaking centers performing alloHSCT in Germany, Austria and Switzerland between November 2018 and March 2020. Twenty-eight (39%) of 72 contacted centers completed the survey, 23 from Germany, two from Austria and three from Switzerland, representing 50% of alloHSCT activity within the participating countries in 2018. Results: All centers reported having nutritional guidelines for patients undergoing alloHSCT, whereby 86% (n = 24) provided a low-microbial diet during the neutropenic phase. The criteria to start parenteral nutrition (PN) directly after alloHSCT seemed to be consistent, 75% (n = 21) of the corresponding centers started PN if the oral nutritional intake or the bodyweight dropped below a certain limit. In the setting of intestinal graft-versus-host disease (GvHD) the current practice appeared to be more heterogenous. About 64% (n = 18) of the centers followed a special diet, added food stepwise modulated by GvHD symptoms, while only four centers regularly stopped oral intake completely (intestinal GvHD grade >1). Half of the centers (54%, n = 15) applied a lactose-free diet, followed by 43% (n = 12) which provided fat- and 18% (n = 5) gluten-free food in patients with intestinal GvHD. Supplementation of micronutrients in acute intestinal GvHD patients was performed by 54% (n = 15) of the centers, whereas vitamin D (89%, n = 25) and vitamin B12 (68%, n = 19) was added regularly independently of the presence of GvHD. Only 5 (18%) participating centers ever observed a food-associated infection during hospitalization, whereas food-associated infections were reported to occur more often in the outpatient setting (64%, n = 18). Conclusion: The survey documented a general consensus about the need for nutritional guidelines for patients undergoing alloHSCT. However, the nutritional treatment in clinical practice (i.e. lactose-, gluten- or fat-free in intestinal GvHD) as well as the use of food supplements was very heterogeneous. In line with current general recommendations the centers seemed to focus on safe food handling practice rather than providing a strict neutropenic diet. More high-quality data are required to provide evidence-based nutrition to patients during and after alloHSCT.